Building Equitable Healthcare Institutions in Low- and Middle-Income Countries: Lessons from Wealthy Nations - Jahun, Ibrahim; Udod, Sonia; Roskoshnyi, Illia; Kurawa, Musbahu Sani; Miko Mohammed, Abdullahi Mustapha (British Journal of Healthcare and Medical Research, 2024)
Healthcare disparity continues to serve as serious obstacle in addressing health needs among disadvantaged populations across the globe. The member states of the Organization of Economic Co-operation and Development (OECD) have attained universal health coverage (UHC) for the past decades, and therefore, there are lessons Low- and Middle-Income Countries (LMICs) can learn from them and contextualize to their settings to strengthen their health systems and minimize healthcare disparities. We reviewed the health system strengthening (HSS) journey of the OECD member states, identified, discussed, and provided recommendations on key HSS pillars that can be adapted by the ten poorest countries to accelerate their health system strengthening efforts toward minimizing healthcare disparities and improving the quality of life for their citizens. The HSS pillars are expansion in healthcare access, improved healthcare spending, demand for more responsive healthcare, cross country study and experience sharing, and prevention policies to promote better health. In the report we also discussed the interwoven relationship between suboptimal governance, pervasive poverty, and fragile health systems in LMICs and suggested how addressing them will pave way to bridging health disparity in LMICs. The strategies and recommendations discussed in the review are critical to enacting good governance, strengthening health systems, and bridging healthcare disparities in LMICs. Strong political will and commitments by the governments of the LMICs, effective, transparent, and accountable partnership with OECD serve as the prerequisites for the strategies and recommendations provided in this report to yield desired impact.